Draft genome sequence of an OXA-23, OXA-66, ADC-25 and TEM-1D co-producing Acinetobacter baumannii ST195 isolated from a patient with neonatal pneumonia in China. (March 2019) - Lv, Weibiao; Zhang, Xiufeng; Hou, Mengtian; Han, Dongdong; Li, Yun; Xiong, Wenguang
Abstract: Objectives: The rapid spread of multidrug-resistant (MDR) Acinetobacter baumannii poses a substantial threat for morbidity and mortality worldwide. In particular, carbapenem-resistant A. baumannii has caused a severe challenge to human health. Here we reported the draft genome sequence of A. baumannii S131434, an OXA-23, OXA-66, ADC-25 and TEM-1D co-producing strain recovered from a patient with neonatal pneumonia in China and belonging to the globally disseminated sequence type 195 (ST195) of clonal complex 92 (CC92). Methods: Genomic DNA was sequenced using an Illumina HiSeq platform and the reads were de novo assembled into contigs using CLC Genomics Workbench. The assembled contigs were annotated and bioinformatics analysis was performed. Results: The genome comprised a circular chromosome of 3 898 344 bp. The presence of the bla OXA-23, bla OXA-66, bla ADC-25 and bla TEM-1D genes was detected. In addition, genes conferring resistance to aminoglycosides, macrolides and tetracycline were also identified. Antimicrobial susceptibility testing revealed that the isolate was resistant to all of the tested antibiotics except for polymyxin B, piperacillin/sulbactam and trimethoprim/sulfamethoxazole. Conclusion: To our knowledge, this is the first report of a clinical A. baumannii ST195 (CC92) isolate producing OXA-23, OXA-66, ADC-25 and TEM-1D in southern China. This draft genome will facilitate further our understanding of the antimicrobial resistance and pathogenic mechanisms in this strain and provides valuable information regarding the colonisation and adaptation of MDR pathogens.